A world view: Considerations of sociocultural diversity in the study of subjective cognitive decline in Alzheimer's disease and related dementias - Mark A. Dubbelman; Tanisha G. Hill‐Jarrett; Silvia Chapman; Gustavo Alves Andrade dos Santos; Martina Azar; Ganesh M. Babulal; Tyler R. Bell; Mark A. Bernard; Carolina Boza‐Calvo; Anthony Q. Briggs; Omonigho Michael Bubu; Heather E. Cuevas; et al. (Alzheimer's & Dementia, 2026)
Abstract Subjective cognitive decline (SCD) refers to cognitive concerns that may occur with or without objective impairment on standardized testing. Studies suggest that SCD may be an early clinical marker of Alzheimer's disease and related dementias, and that it can predict future objective cognitive decline and progression to dementia. However, the research that supports these conclusions is primarily based on samples with homogeneous socioeconomic and cultural backgrounds. The limited studies in samples with more diverse representations of racial, ethnic, gender, and sexual orientation characteristics show varying SCD prevalence, correlates, and outcomes. Here, we review this literature, focusing on how to apply the findings to advance our understanding of SCD. We further evaluate how our findings inform a roadmap for future research. Overall, we conclude that broader investigations across more diverse populations enhance our understanding of the factors that may differentially contribute to SCD and shape its utility as a clinical metric.